(untitled) (INNOVATIVE ECONOMY, 2023)
Svynous I.V., Hnatyshyna L.B., Havryk O.Yu., Cherepenchuk T.Ya. ORGANIZATIONAL APPROACHES TO IMPROVING THE ACCOUNTING AND ANALYTICAL SYSTEM AT AGRICULTURAL ENTERPRISES Purpose. The aim of the article is the development of practical recommendations for improving the accounting and analytical system at agricultural enterprises in the conditions of accounting reform based on the generalization of research by scientists. Methodology of research. In the research process, an epistemological method was used to clarify and deepen the content of concepts and categories in the field of accounting and analytical support of agricultural enterprises. Analysis, synthesis, induction, deduction, abstraction, idealization and generalization as methods of scientific knowledge are applied to the development of the provisions of the theory, methodology and practice of accounting in the system of information support for the activities of economic entities in the field of agrarian business. Findings. On the basis of the conducted research, practical recommendations are proposed for the construction of an information and accounting system of an agricultural enterprise, which is based on intra-farm (management) reporting, which is formed on the data of primary and management accounting registers. It is proven that the introduction of the budgeting system in terms of responsibility centres - structural units will ensure the assessment of the effectiveness of the use of input material costs and the search for reserves to reduce production costs in the process of production and sale of products by farms of the corporate sector of the agrarian economy. Originality. Practical recommendations for the preparation of management reporting of an agricultural enterprise, which are based on the specifics of the enterprise’s activity, as well as the specifics of the work of a specific structural unit, centre of responsibility, or activity segment, are substantiated. Methodical approaches to the segmentation of the activities of farms in the corporate sector of the agrarian economy have been improved, which will ensure the integrity of the accounting and analytical system, which is based on a complex combination of primary and management accounting and intra-farm (management) reporting. Practical value. The introduction of elements of intra-farm (management) accounting into activities, in particular the management report on the activity of responsibility centres - structural subdivisions, will provide an assessment of the effectiveness of the use of material resources in the production of agricultural products and the identification of reserves for reducing their cost price. Key words: agricultural enterprise, management accounting, accounting system, reporting, costs.